A randomised, placebo-controlled study of omipalisib (PI3K/mTOR) in idiopathic pulmonary fibrosis. Issue 3 (19th March 2019) - Lukey, Pauline T.; Harrison, Stephen A.; Yang, Shuying; Man, Yim; Holman, Beverley F.; Rashidnasab, Alaleh; Azzopardi, Gabrielle; Grayer, Michael; Simpson, Juliet K.; Bareille, Philippe; Paul, Lyn; Woodcock, Hannah V.; et al.
Phosphatidylinositol 3-kinases (PI3Ks) and mammalian target of rapamycin (mTOR) play a role in the pathogenesis of idiopathic pulmonary fibrosis (IPF). Omipalisib (GSK2126458) is a potent inhibitor of PI3K/mTOR. A randomised, placebo-controlled, double-blind, repeat dose escalation, experimental medicine study of omipalisib in subjects with IPF was conducted (NCT01725139) to test safety, tolerability, pharmacokinetics and pharmacodynamics. Omipalisib was dosed at 0.25 mg, 1 mg and 2 mg twice daily for 8 days in four cohorts of four subjects randomised 3:1 to receive omipalisib or placebo (two cohorts received 2 mg twice daily). 17 subjects with IPF were enrolled. The most common adverse event was diarrhoea, which was reported by four participants. Dose-related increases in insulin and glucose were observed. Pharmacokinetic analysis demonstrated that exposure in the blood predicts lung exposure. Exposure-dependent inhibition of phosphatidylinositol 3, 4, 5 trisphosphate and pAKT confirmed target engagement in blood and lungs. 18 F-2 - fluoro-2-deoxy-d -glucose(FDG)-positron emission tomography/computed tomography scans revealed an exposure-dependent reduction in 18 F-FDG uptake in fibrotic areas of the lung, as measured by target-to-background, ratio thus confirming pharmacodynamic activity. This experimental medicine study demonstrates acceptable tolerability of omipalisib in subjects with IPF at exposures for which target engagement was confirmed both systemically and in the lungs. Omipalisib, a PI3K/mTOR inhibitor, engages the target systemically and in the lungs of subjects with IPF. These effects were demonstrated in an experimental medicine study and were measured by inhibition of pAKT/AKT, PIP3/PIP2 and 18 F-FDG-PET. http://ow.ly/7dMu30mZvcS